Human Rights and Neoliberalism in Australian Welfare to Work Policy: Experiences and Perceptions of People with Disabilities and Disability Stakeholders - Sarah Parker Harris; Randall Owen; Karen R Fisher; Robert Gould (Disability Studies Quarterly, 2014)
Recent policy approaches in Australia, influenced by neoliberalism, have constrained the implementation of international disability rights at the national level. Within the neoliberal and human rights approaches to social policy, what is the lived experience of people with disabilities? In focus groups with people with disabilities and interviews with disability stakeholders in Australia, participants were asked about their experiences and perspectives of welfare to work programs. We analyzed the data by drawing on the United Nations Convention on the Rights of Persons with Disabilities as a framework. The analysis revealed tensions between the rights and responsibilities of citizens and the government, and a disconnection between policy discourse and policy practice. The results suggest that disability rights are jeopardized unless governments take responsibility to create the policy environment for rights-based policy to be implemented; including the equalization of opportunities, providing accessible information and communication about employment, and addressing the administration and process practices that employment service providers follow.
Keywords: Disability; Employment; Human Rights; Neoliberalism; Qualitative